Politics of English Translation: Exploring the Transition of Kannada Classics into Global Discourse - Mitra, A. (University of Jaffna, 2025)
Since the 2000s, there has been an increased interest among regional authors and translation scholars in bringing the classics of regional languages into English. Numerous projects, often in association with universities, have been launched with the intent of showcasing and positioning local cultures on the global stage. However, this trend has also unveiled the inherent politics of translation, raising concerns about the distortion of ancient texts when presented in a language and cultural context that differs from their origin. This paper explores the politics and theories of translation by focusing on the Kannada classics The Life of Harishchandra by Raghavanka (translated by Prof. Vanamala Vishwanatha) and The Kannada Mahabharata (translated by S.N. Shridhar and team). These works, translated as part of the monumental Murty Classical Library of India project, serve as case studies to analyze how ancient texts are reinterpreted and represented during the translation process. The study engages with translation theories, including Eugene Nida’s “dynamic equivalence,” Lawrence Venuti’s “domestication and foreignization,” and Walter Benjamin’s concept of “the task of the translator,” to critically evaluate the transformation of these texts. It examines how stylistic nuances intrinsic to Kannada literature—such as poetic rhythms and cultural idioms—are often simplified or paraphrased in English translations, leading to a potential loss of primordial literary essence. By tracing the trajectory of these texts from their Kannada origins to their English renditions, this paper interrogates the interplay between visibility, global representation, and the compromises made in translation. The analysis underscores how the pursuit of global recognition often sacrifices the richness of local literature, thereby perpetuating a politics of representation that shapes the reception and legacy of regional classics.
Keywords: Translation; Kannada classics; Politics of representation; Global discourse